Determinants of Compliance of Mothers on Vaccine Preventable Diseases (VPD) Immunization at the Rural Health Units of the 5th District of Camarines Sur - M. Dacara, Jhessa; Malabanan, Leni Moralde (Journal of Public Health Sciences, 2025)
The study examined the determinants of compliance with vaccine preventable diseases (VPD) immunization among mothers with children aged ≥1 year in the rural health units of the 5th District of Camarines Sur, Philippines. The research utilized a descriptive analytical research design employing a questionnaire to gather data. The findings reveal a diverse demographic profile among the respondents, highlighting factors such as age, civil status, religion, number of children, educational background, occupation, and family income. The study indicates a strong commitment to vaccination practices among mothers, with notable emphasis on prioritizing immunization appointments and recognizing the importance of vaccination for preventive healthcare. Factors influencing compliance include access to healthcare services, knowledge and awareness about vaccines, attitudes and beliefs, socio-economic status, and the availability of healthcare infrastructure. Religion and family monthly income emerged as significant predictors of compliance, underscoring their impact on immunization adherence.  Based on the study's results, a proposed plan to enhance compliance focuses on educational campaigns, improved accessibility, personalized support, and incentives for mothers. By addressing these areas, the plan aims to increase vaccination rates and ensure effective implementation of VPD immunization programs.